The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/vetsci9050242
|View full text |Cite
|
Sign up to set email alerts
|

Dog Handler Beliefs regarding Barriers and Facilitators to Canine Health Promotion and Injury Prevention in Swedish Working Dog Trials and Competitions

Abstract: Dog trials and competitions involve various sport disciplines, e.g., obedience, agility, working dog trials and rally obedience. Dog handlers navigate their dogs through physically and mentally demanding tasks. The purpose of this study was to gain a better understanding of barriers and facilitators to canine health promotion and injury prevention described by dog handlers. Methods: Qualitative inductive content analysis was applied to systematically organize and interpret narrative data from 654 respondents’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The final version of the questionnaire contained mainly close-ended multiple choice questions in Swedish. The results from a qualitative content analysis of narrative data from open-ended questions in the survey have been published elsewhere ( 59 ). The survey was distributed by means of an internet survey site (Google Forms, Google LLC, Mountain View, CA, USA) to facilitate data collection.…”
Section: Methodsmentioning
confidence: 99%
“…The final version of the questionnaire contained mainly close-ended multiple choice questions in Swedish. The results from a qualitative content analysis of narrative data from open-ended questions in the survey have been published elsewhere ( 59 ). The survey was distributed by means of an internet survey site (Google Forms, Google LLC, Mountain View, CA, USA) to facilitate data collection.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted with competitive sporting and utility trial dogs (n = 1582) using reported data from an online questionnaire survey completed by dog handlers [29,47]. The questionnaire examined the demographic variables of the dog, e.g., sex, age, body weight, breed, and sports-related variables, e.g., participation in various disciplines, health history, and return to competition.…”
Section: Dogs and Data Collectionmentioning
confidence: 99%
“…We have previously reported on dog handlers' beliefs with regard to competitive tasks [29]. Tasks that were considered barriers to canine health by the dog handlers' and potentially harmful for the dogs were crawling, staying in a group with other dogs, protection work, high ladder, heavy retrieving, jumping obstacles, and gun shots.…”
Section: Onset Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…A dog with good physical fitness has a better capability to perform its task, which also reduces the risk of injury; hence, the ability to measure the dog’s fitness level is imperative. With the increasing number of pets and working dogs, owners’ interest in the well-being of their dogs is also on the rise [ 51 , 52 , 53 , 54 , 55 ]. Providing fitness-related information to dog owners can affect their dog handling and exercising habits and thereby contribute to the well-being of dogs.…”
Section: Introductionmentioning
confidence: 99%